Location determinants of high-growth firms. Issue 1 (1st January 2016) - Li, Minghao; Goetz, Stephan J.; Partridge, Mark; Fleming, David A.
Abstract: County-level location patterns of INC 5000 companies provide one map of American entrepreneurship and innovativeness, and understanding the local factors associated with these firms' emergence is important for stimulating regional economic growth and innovation. We draw on the knowledge spillover theory of entrepreneurship to motivate our regression model, and augment this theory with additional regional features that have been found to be important in the firm location literature. Zero-inflated negative binomial regressions indicate that these firms exist in counties with larger average establishment size, higher educational attainment and more natural amenities. Income growth, a mix of higher paying industries, and more banks per capita are associated with a smaller presence of these types of firms, all else equal. We conclude that the local conditions favouring high-growth firms are likely to be different from those favouring new firms in general, and that these conditions differ significantly in urban and rural areas and by industrial sectors.